THE 15TH CONGRESS OF PEDIATRICIANS OF RUSSIA WITH INTERNATIONAL COLLABORATION «ACTUAL PROBLEMS IN PEDIATRICS» (MOSCOW, 14-17 FEBRUARY 2011) - T.M. Автор ("Paediatrician" Publishers LLC, 2011)
(Voprosy sovremennoi pediatrii - Current Pediatrics. 2011; 10 (2): 220-224)